Empowering Women Victims of Sexual Violence in Bandung City - Saputri Lisnawati (Wadah Inovasi Indonesia, 2023)
The purpose of this research is to find out the empowerment of women victims of sexual violence in Bandung City. This research uses a qualitative approach with in-depth interviews as a data collection method. The research subjects consisted of women who were victims of sexual violence in Bandung City and had participated in existing empowerment programs. The researcher conducted a thematic analysis of the collected data to identify themes and patterns that emerged in the empowerment experience of women victims of sexual violence. Based on the thematic analysis, this study found several important findings. First, the empowerment program for women victims of sexual violence in Bandung City has a positive impact in increasing their independence and self-confidence. Local community involvement and social support also play an important role in the empowerment process. Second, challenges faced by women victims of sexual violence include social stigma, limited access to health and financial services, and lack of trust in the legal system. Third, women's active participation in decision-making and advocacy for their rights are key to their empowerment. This study concludes that empowering women victims of sexual violence in Bandung City is an effective approach to help them recover holistically. Although this study provides a better understanding of the empowerment of women victims of sexual violence in Bandung City, there are still some gaps that can be the direction of future research. One such gap is the need for further research on the influence of cultural and social factors in the empowerment of women victims of sexual violence in the context of Bandung city.